Pengaruh Harga dan Promosi Digital terhadap Keputusan Pembelian Konsumen pada Online Shop Perlengkapan Bayi Lanugo Baby Jakarta Barat - Silvi Nur Octaviani; Rakhmat Hadi Sucipto; Tri Indah Annisa (Ebisnis Manajemen, 2025)
This research investigates the effect of price and digital promotion on consumer purchasing decisions at the online baby supply store “Lanugo Baby” in West Jakarta. Employing a quantitative research design, the study applies multiple linear regression analysis to assess the relationships between variables. Data collection was carried out by distributing questionnaires to 30 respondents chosen through purposive sampling, and the data were subsequently tested using validity and reliability checks, t-test, F-test, as well as classical assumption tests to ensure accuracy and consistency. The empirical results reveal that both price and digital promotion positively and significantly influence consumer purchase decisions, whether examined individually or simultaneously. Furthermore, the coefficient of determination (R²) value of 0.536 demonstrates that 53.6% of the variation in purchase decisions can be explained by the two independent variables studied, while the remaining proportion is influenced by other factors not included in the model. These findings emphasize the necessity for online baby product stores to adopt competitive pricing strategies alongside effective digital marketing campaigns in order to capture consumer interest and strengthen purchase intentions. In a highly dynamic marketplace, the integration of fair pricing with creative digital promotion can improve competitiveness, build consumer trust, and ultimately enhance overall purchasing behavior.